2016
DOI: 10.1093/schbul/sbw113
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia and Infections: The Eyes Have It

Abstract: The visual tract is prominently involved in schizophrenia, as evidenced by perceptual distortions and a type of nystagmus found in many individuals affected. Genetic explanations for these abnormalities have been suggested. This study proposes an alternate explanation based on infection. Several infectious agents thought to be associated with some cases of schizophrenia are known to cause both infection of the fetus and abnormalities of the eye. Toxoplasma gondii is examined in detail, and rubella, cytomegalov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…(2) The strength of the effect positively correlated with the intensity of exposure to the suspected risk factor, here the intensity of sustained animal-related injuries. (3) The cats and dogs are vectors of some pathogens that are known to have negative impacts on human mental health [37, 56, 61]. In the present study we showed that Toxoplasma was not the cause of the observed associations between the injuries and impaired health of the responders [56].…”
Section: Discussionmentioning
confidence: 54%
“…(2) The strength of the effect positively correlated with the intensity of exposure to the suspected risk factor, here the intensity of sustained animal-related injuries. (3) The cats and dogs are vectors of some pathogens that are known to have negative impacts on human mental health [37, 56, 61]. In the present study we showed that Toxoplasma was not the cause of the observed associations between the injuries and impaired health of the responders [56].…”
Section: Discussionmentioning
confidence: 54%
“…However recently studies have documented that tissue cysts are engaged in active metabolism and interaction with the host [ 1 ]. Accordingly, serological studies indicate that exposure to Toxoplasma can be associated with eye disease [ 2 ] as well as an increased risk of a range of neuropsychiatric diseases including schizophrenia[ 3 , 4 ], bipolar disorder[ 5 ], suicidal behavior[ 6 ], anxiety disorder [ 7 ] and cognitive decline in the elderly [ 8 ] in some populations. The factors which determine why some Toxoplasma exposed individuals develop medical or psychiatric disorders while others are unaffected have not been determined but may related to the strain of Toxoplasma, host factors, or the timing of infection.…”
Section: Introductionmentioning
confidence: 99%
“…39 Ocular infections with the parasitic apicomplexan T. gondii, associated to substantial increases in OST, might explain some of the perceptual distortions experienced in schizophrenia. 42 Drug-free SCZ patients showed 1.55 C higher corneal temperatures when compared to matched controls. 43 Another study reported that the corneal temperature of neuroleptic-treated patients was signicantly lower than that of the drug-free patients.…”
Section: Introductionmentioning
confidence: 90%